The Relationship Between Knowledge Of Mothers Of Toddlers About Posyandu On The Activeness Of Mothers Of Toddlers - Frenky Arif Budiman; Siti Fadilah (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: Posyandu stands for integrated service post as a place of service from and by the community with community targets managed by the community with support from health workers, especially for toddlers and pregnant women.Research Methods: The design used is correlational analytic with a cross-sectional approach. A population of as many as 63 mothers of toddlers with a stratified sectional sampling technique obtained a sample of 41 respondents. The instrument used Questionnaire data analysis using Spearman Rank Correlation Statistical Test Independent and dependent variables with the Simple Random Sampling method. Research Result: Knowledge of mothers of toddlers about posyandu based on the results of filling out the Questionnaire has good criteria (12.2%), enough (17.1%), and less (70.7%). The activeness of the visit of mothers of toddlers coming to Poland in Sambirejo Village, Pare District, Kediri Regency, the results obtained 63.4% had a good level of activeness, and 36.6% had not good activeness. Conclusion: The results of data analysis with the Spearman rank test obtained a P-value = 0.123>0.05, which means there is no relationship between maternal knowledge and the activeness of mothers of toddlers in Sambirejo Village, Pare District, Kediri Regency.